Bone marrow-derived myeloid cells drive neuroinflammation in Alzheimer's disease: Insights from the FAD4T mouse model - Yidan Pang; Dongjing Jia; Fang Ye; Fei Liu; Jiaqi Li; Siyuan Zhu; Bingqi Wang; Meng Yao; Lin Du; Chunying Yang; Guoji Guo; Cunxiang Ju; et al. (Journal of Orthopaedic Translation, 2025)
Objective: Alzheimer's disease (AD) is marked by amyloid β (Aβ) accumulation, neuroinflammation, and cognitive decline. While neuroinflammation is a key feature of AD, the potential involvement of bone marrow-derived cells in its pathology remains unclear. This study aimed to investigate the role of bone marrow-derived myeloid cells in driving neuroinflammation in AD. Methods: We developed a transgenic mouse model (FAD4T) by overexpressing human APPSwe/Ind and PSEN1 M146L/L286V on a C57BL/6J background. FAD4T mice were characterized for hallmark AD features, including amyloid deposition, glial activation, and cognitive deficits. Additionally, single-cell transcriptomic analysis was performed to profile bone marrow and brain myeloid cells. Bone marrow transplantation experiments were conducted to assess the contribution of bone marrow-derived macrophages to neuroinflammation in AD. Results: FAD4T mice exhibited hallmark AD phenotypes such as amyloid deposition, glial activation, and cognitive impairment, alongside osteoporosis-like changes. Single-cell transcriptomic analysis identified a significant increase in bone marrow-derived macrophages in the brains of FAD4T mice. These cells showed upregulation of AD-related genes, including Cst7 and Ctsd, suggesting their active role in neuroinflammation. Bone marrow transplantation experiments further confirmed that bone marrow-derived macrophages contributed to the inflammatory processes in the AD brain. Conclusion: Our findings demonstrate that bone marrow-derived myeloid cells infiltrate the brain and might play a critical role in driving neuroinflammation in AD. Targeting these cells may represent a novel therapeutic strategy for mitigating inflammation and disease progression in AD. The translational potential of this article: Our findings suggest that bone marrow-derived inflammation play a critical role in AD-associated inflammation, offering potential targets for therapeutic intervention such as Cst7 and Ctsd in bone marrow-derived myeloid cells.